Adaptive Packet Tuning for Energy Efficient Communication in Underlay CSMA/CA Networks - Minchae Jung; Jonghun Han (IEEE Access)
The demand for wireless connectivity has increased recently, driven primarily by Internet of Things (IoTs) and 6G applications. Since various wireless networks operate on an unlicensed band and coexist with upcoming IoT networks, undesired interference in IoT networks from other networks is inevitable. In addition, interference heavily affects the lifetime of IoT networks owing to their limited battery capacity. However, the interference of underlay networks in hierarchical coexisting networks has not yet been analyzed and its impact on energy efficiency remains uncharacterized. In this paper, the energy efficiency of the underlay network is statistically analyzed in the presence of interference from a coexisting overlay network. Based on our analyses, a closed-form expression for the average energy efficiency of the underlay network is derived and a packet size that maximizes the average energy efficiency is then proposed. The results of our analyses are consistent with the actual results, confirming that both the average energy efficiency of the underlay network and its optimal packet size can be readily obtained using our analyses without the need for extensive simulations. Simulation results confirmed the validity of the our statistical analyses. The simulation results demonstrate that our analyses can accurately and analytically determine the energy efficiency of the underlay network, and the proposed packet size can achieve more than 99 % of the optimal performance. The feasibility of adaptive packet tuning is also verified using actual overlay packet traces as inputs for our simulation.